Effects of Principal Skills, Work Culture, Learning Facilities on Primary School Teacher Performance - Anis Syamsu Rizal; Nurjaya Nurjaya (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2020)
The purpose of this study was to analyze the principal's skills on teacher performance; cultural influences on teacher performance; the effect of learning facilities on teacher performance; and the motivation to learn from the principal, work culture and learning facilities together on teacher performance. The study was conducted on 86 elementary school teachers at the Tadika Puri Foundation in South Jakarta, data were collected through a questionnaire distributed to respondents, while open interviews were conducted with Foundation administrators. Data analysis use SPSS application assistance. The research findings show that there are principals 'skills on teacher performance, there is a development of work culture towards teacher performance, there is development of learning facilities on teacher performance, and there is development of principals' skills, work culture, and joint learning development on teacher performance.